'Ora Minggir Tabrak' Electronic Dance Music (EDM), a Montage of The Time-Image - Citra Aryandari (Institut Seni Indonesia Yogyakarta, 2018)
Electronic Dance Music (EDM) is a music genre which has been perceived in negative way because closely related to night life in which alcoholic drinks and illegal drugs. The beatings of the rhythm presented can arouse a desire to shake the body, giving instant pleasure to escape from the weariness of life. Although it could be said that this music genre is able to help the listeners to forget “the problems” of life, however, it is very rarely that the academic circle looked into this music genre and make it as a subject of interesting studies. This article is written out of subjective observations in social sphere on subjects containing a lot of secrecies and initially considered as a taboo to be discussed. The existence of EDM in line with the technological developments as montage of the time-image related with complexity of social relations, attempting to embark on a new identity in power, politics, and ideological trappings. The phenomenon comes into sight specifically in the song of “Ora Minggir Tabrak”,literally means if you get on my way I will hit you, a soundtrack of Ada Apa Dengan Cinta 2feature film. And it obviously could be seen in talent hunting for EDM musicians program broadcast by Net TV (the ReMix), and several other big events with internationally standard organized annually, such as DWP (Djakarta Warehouse Project); and Dreamfield at GWK Bali, which are worth-discussing amidst the hustle and bustle of music market in Indonesia.